Clinicians' attitude towards a placebo-controlled randomised clinical trial investigating the effect of neuraminidase inhibitors in adults hospitalised with influenza - Bradbury, Naomi; Nguyen-Van-Tam, Jonathan S.; Lim, Wei Shen (BioMed Central, 2018)
Background: The value of neuraminidase inhibitors (NAIs) in reducing severe clinical outcomes from influenza is debated. A clinical trial to generate better evidence is desirable. However, it is unknown whether UK clinicians would support a placebo controlled trial. A survey was conducted to determine the attitude of clinicians towards a clinical trial and their current practice in managing adults admitted to hospital with suspected influenza.